“Men Need Role Models”: Exploring the Facilitators and Barriers for Yoga Participation Among Men - Jonathan Y. Cagas; Stuart J. H. Biddle; Oscar Castro; Ineke Vergeer (American Journal of Men's Health)
Yoga is a holistic form of physical activity taken up for various reasons, including physical and mental health, and sometimes spirituality. Despite the growing popularity of yoga as a form of health-enhancing physical activity, data show the uptake among men to be consistently low compared to women. To gain an understanding of barriers and facilitators for yoga uptake and adherence among men, four focus group discussions (three male groups, one female group) and three individual interviews were undertaken. Using thematic analysis, three themes were developed: (a) encouragement, advice, and support from trusted others, (b) confronting gender-related perceptions and issues, and (c) getting to the benefits. The findings suggest that men are more likely to take up yoga when encouraged by trusted others and male role models. Men face gender-related challenges that can be overcome by educating them about yoga, focusing on its physical benefits, and experiencing the benefits of yoga firsthand. To encourage more men into yoga, yoga teachers need to create an inclusive environment that welcomes men and caters to their needs. These findings provide valuable insight into the unique challenges experienced by men in pursuing and practicing yoga regularly. They may be used to develop targeted recruitment and marketing strategies to draw more men into yoga and encourage them to stay, which is essential for experiencing the many long-term health benefits of yoga.